The hermeneutical self and an ethical difference: intercivilizational engagement - Chung, Paul S. (James Clarke and Co, 2012)
Part I. Hermeneutical theory and human experience. Interpretation and experience -- Interpretation and life connection -- Phenomenology and hermeneutics -- Understanding and linguistic existence -- Part II. Intercivilizational encounters : interpretation and ethical subject. Mediation : the hermeneutical self and moral self -- Interpretation and ethics of virtue : Aristotle revisited -- Intercivilizational encounters : the mean in Confucian ethics -- Thomas Aquinas : theological virtue ethics and analogy -- A comparative religious study of Aquinas and Mengzi -- Part III. Aftermath of modernity : discourse reason and ethics of the other. Interpretation in long route and social location -- Discourse ethics and communicative rationality -- Neo-Aristotelian ethics and neo-Kantian framework -- Aesthetics of existence and ethics of alterity -- Part IV. Intercivilizational reconstruction in the aftermath of colonialism. Intercivilizational reconstruction and global-critical inquiry -- Engaging the Cave and the Butterfly : dialectics of Enlightenment and neo-Confucian self -- Interpretations as conflict and creativity : retrieval of Wang Yangming -- Concluding reflection : the hermeneutical self and an ethical difference -- Epilogue: Interpretive reason and postcolonial irregularity.